Identification of Nasonov Pheromones and the Effects of Synthetic Pheromones on the Clustering Activity of the Asiatic Honeybee (APis Cerana) - Abdullah, NurHani; Hamzah, Asiah; Ramli, Johari; Mardan, Makhzir (1980)
Worker bees from several Apis cerana colonies were sampled for identification ofNasonov secretions and their clustering activity in 1°esponse to different synthetic components of the swarming pheromones. Extraction of Nasonov gland secretion was canied (mt try three methods - Abdomen Dippingmethod, Excised Gland method and S)'ringe Extmction method - and its anal),sis was canied out b), Gas Liquid Chromatograph),. Nasonov components delected were (E)-citml, (Z)-citml and g~ranioL However, onl), (E)-citml and geraniol were quantified. The Abdoment Dipping method detected 20.0 ug per bee oj (E) -citral, whereas the Excised Gland method detected onl), 3.8 ug. Geraniol was onI)' detected try the latter technique at 2.5 ng Plff bee. (Z) -citral was detected in t·race amounts. The clustering experiments were conducted in a confined darkened room at room temperat1m. Chemical components, consisting of 9-oxo-2-decenoic acid designated as 9ODA, (E), (Z)-citral, geraniol, nerol andfarnesol, were tested either singly or in vmious combinations. Each component or mixtures of these componenls were adsorbed on afilterpaperplaced in alighted peifomted ca,.dboard cannister. Five cannislen were used in each tlial. Among the synthetic compon""ts tested, the (E), (Z) -citral was[oltnd to be most effective in attracting w01*er bees to fonn a clustero